Environmental biotechnology a biosystems approach - Vallero, Daniel A. (Academic Press, 2016)
"This single volume takes a biosystems approach to explore and explain the scientific and engineering principles and practices needed to understand the complexities of environmental biotechnology. Thoroughly covering physical, chemical and biological principles that support biotechnologies, Environmental Biotechnology's readable text and ample figures and tables provide a scientifically credible basis for an introduction to environmental biochemodynamics. Integrated with discussions of actual and potential risks of various biotechnologies on the environment, this book provides a context for researchers, practitioners, and students in previously disparate disciplines such as microbiology, systems biology, environmental engineering, risk assessment, ecology and genetic engineering to critically assess the efficacy and long-term effects of biotechnologies on the environment"--Provided by publisher.